Pengujian Struktur Mikro dan Kekerasan Plat Baja Karbon Rendah Dengan Suhu 9000C Di Quenching Dengan Air Kelapa dan Air Tebu - Ahmadin Ahmadin; Erizal Erizal (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2022)
Abstract Mechanical properties of non-treated low carbon steel plate and materials that received heat treatment at 9000 C by quenching coconut water and sugarcane juice obtained from the test results, based on hardness testing obtained from Brinell in the Bengkulu University laboratory with an average result without treatment = 59, 76 HRB, sugarcane juice quenching = 64.4 HRB, coconut water quenching = 65.06 HRB, Based on the above test it can be concluded that the specimens that received heat treatment and quenched with coconut water had the highest hardness value compared to specimens that received heat treatment and quenched with sugarcane juice and specimens without getting any treatment. As for the microstructure grains obtained in the specimen on the right, the untreated specimen = 10.9 µm, the coconut water quenched specimen = 10.4 µmand the sugarcane juice quenched specimen = 8.6 µmwhile on the left the grains microstructure grains obtained from untreated specimens = 11.25 µm, coconut water quenched specimens = 10.3 µm and sugarcane juice quenched specimens = 8.5 µmwhile on the left